Postmodernidad y educación. La teoría de Toffler y la práctica de la C.M.U - Colom Cañellas, Antoni J.; MÈlich, Joan-Carles (Teoría de la Educación. Revista Interuniversitaria, 2009)
The aim of this article is to analyse the relationships among postmodern philosophy and education. The writers review the idees of Nietzsche in order to link it with the sociotecnich proposition of Toffler, and to end it with the practic of Carnegie-Mellon University, as an example of educational action in postmodernity.